BENEFICIAL EFFECT OF LIMING TO GREEN GRAM AND SPINACH IN ACID SOILS OF ZAHEERABAD DIVISION IN SANGAREDDY DISTRICT OF TELANGANA - M. CHANDINI PATNAIK; K. P. VANI, EVELYN LALPARMAWII, M. SHANKARAIAH (The Journal of Research, PJTSAU, 2023)
An investigation entitled “Beneficial effect of liming to green gram and spinach in acid soil of Zaheerabad division in Sangareddy district of Telangana” was carried out at Agricultural Research Institute (ARI), Rajendranagar to study the beneficial effect of liming and FYM as well as suitable combination of nutrients with and without lime and FYM in acid soils and it’s beneficial effect to green gram and spinach. Incubation of acid soils with lime and FYM for 15 days, 30 days, 45 days and 60 days influenced soil pH and nutrient availability. It was observed that soil pH increases with increasing a period of incubation from 15 to 60 days, where highest (pH 7.01) in 60 days of incubation with T3 -lime. Available nitrogen increases with a period of incubation, available phosphorus increases with a period of incubation and gradually decrease in 45 days, available potassium increased till 30 days and gradually decreased at 45 days of incubation with application of lime and FYM. Exchangeable calcium is highly at 15 days of incubation and gradually decreased with increasing a period of incubation, and the highest is observed in 15 days (2.30 cmol kg-1) with application of lime.A pot culture experiment was conducted employing six treatments, T1- RDF, T2 - FYM @10 t ha-1, T3 - Lime, T4 - RDF+FYM, T5 - RDF+ lime and T6 - RDF + FYM+ lime. Applications of RDF+ FYM+ lime resulted in highest grain yield of green gram (5.11 g pot-1) and dry matter of spinach (12.23 g pot-1). Acid soils treated with lime and FYM alone observed to significantly increased yield of green gram and spinach. The best results were obtained in combined application of lime along with FYM @10 t ha-1 and RDF. Application of lime and FYM resulted in significant increase in nutrient content as well as uptake in both green gram and spinach. Nitrogen, Phosphorus and Potassium content and uptake increases with applications of lime and FYM. The highest content and uptake were resulted in RDF + FYM@ 10 t ha-1+ lime. Among the micronutrients, manganese content and its uptake by green gram and spinach decreased where zinc and copper gradually increase with applications of lime and FYM, respectively. Applications of lime increased the soil pH in acid soils, with the highest from 4.98 to 7.01 and 5.32 to 6.93. It was observed that acid soil treated with lime significantly effect the nutrients availability. A vailable nitrogen, phosphorus, potassium, sulphur and exchangeable calcium & magnesium increased whereas, available manganese and iron decreased with application of lime in acid soils. Application of lime significantly increased exchangeable calcium from 0.87 to 2.15 cmol kg-1 and exchangeable magnesium from 0.12 to 1.61 cmol kg-1. Available manganese decreased from 26.6 to 22.7 mg kg-1 and available iron from 11.76 to 8.05 mg kg-1, respectively. From the results obtained, it is concluded that liming and FYM significantly increased yield of green gram and spinach in acid soils. Application of lime along with FYM and RDF increased the availability of essential nutrients.